Scheduling Strategies Evaluation for Opportunistic Grids - Gomes, Berto de Tacio Pereira; Cunha Filho, Gilberto; Campos, Igor Ramos; Gonçalves, Jesseildo; Silva, Francisco José da Silva e (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2010: Anais do XI Simpósio em Sistemas Computacionais de Alto Desempenho, 2010)
On this work we evaluate scheduling strategies usually applied on heterogeneous distributed environments, taking into consideration the characteristics of opportunistic grids. On the explored scenarios, several parameters are considered and correlated, such as application arrival rate, the occurrence of failures, application tasks size and heterogeneity, and the time to recover from application failures.